"Assessing Government Regulation No. 45/1990 through the Lens of John Rawls' Theory of Justice: Implications of Polygamy Prohibition for Female Civil Servants" - Sarifah Alawiyah (QURU’: Journal of Family Law and Culture, 2025)
Basically, regulations are made to provide benefits and guarantee the rights of individual humans. In fact, the practice of polygamy is the right of everyone, both men and women, because polygamy itself is not prohibited even though it must fulfil certain conditions. In order to create this goal, legal protection must be provided. However, this protection is still inadequate, especially for women. In Article 4 paragraph (2) of Government Regulation Number 45 of 1990, female civil servants are not given the right to choose a life partner because it is prohibited in the regulation. The purpose of this article is to analyse the extent to which the existence of the regulation really provides justice from the perspective of John Rawls' theory and what is the background of a woman who works as a civil servant is prohibited from polygamy? 2) and how does John Rawls' theory of justice review the prohibition of polygamous civil servant women based on Government Regulation Number 45 of 1990? This research uses qualitative methods, while this type of research is literature, with a normative juridical approach. The conclusion of this article is that the prohibition of polygamous female civil servants is motivated by factors of employment status, factors of disruption of work duties and responsibilities, and behaviour and actions. The existence of PP Number 45 of 1990 is actually contrary to John Rawls' theory of justice in the Principle of Equal Liberty aspect, as evidenced by the fact that the regulation does not allow a woman to choose a life partner even as a second wife. This proves that the regulation does not accommodate human rights because marriage is the right of every citizen. Meanwhile, in the aspect of The Principle of Difference, the existence of these rules is also contradictory. It is proven that the existence of these rules provides a gap for a man to be polygamous and closes the gap for women to be polygamous. This makes a difference in regulations in treating men and women.  Because the principle of difference actually realises justice without discriminating between sexes.